Does Good Governance Mediate Relationship Between E-Government and Public Trust in Lebanon? - Alaaraj, Hassan; Hassan, Sallahudin (International Review of Management and Marketing, 2016)
The main objective of this research is to study the mediating effect of good governance on the relationship between e-government practices and public trust in Lebanon. Based on extensive literature review and conceptual background including the theories of institutional-based trust and the diffusion of innovation, the theoretical research framework was developed. Primary data was collected using survey involving 400 Lebanese employees from different small and medium enterprises in Beirut. The data have been analyzed using Structural Equation Modeling (SEM). The research findings revealed that eight hypotheses were accepted while five hypotheses were rejected. This research contributes practically by offering policy makers in governments the guidelines to empower and build citizens' trust by providing efficient, transparent and accountable government services. Future studies are suggested to extend the research empirically in terms of type of respondents, geographical location and analytical methods. Keywords: E-government, good governance, public trust, Lebanon JEL Classifications: H00; O1; O3